A Security Scheme for Dependable Key Insertion in Mobile Embedded Devices. (22nd March 2011) - Klimm, Alexander; Glas, Benjamin; Wachs, Matthias; Vogel, Sebastian; Müller-Glaser, Klaus D.; Becker, Jürgen
Abstract : Public Key Cryptography enables entity authentication protocols based on a platform's knowledge of other platforms' public key. This is particularly advantageous for embedded systems, such as FPGA platforms, with limited or none read-protected memory resources. For access control systems, an access token is authenticated by the mobile system. Only the public key of authorized tokens needs to be stored inside the mobile platform. At some point during the platform's lifetime, these might need to be updated in the field due to loss or damage of tokens. This paper proposes a holistic approach for an automotive access control system based on Public Key Cryptography. Next to a FPGA-based hardware architecture, we focus on a secure scheme for key flashing of public keys to highly mobile systems. The main goal of the proposed scheme is the minimization of online dependencies to Trusted Third Parties, Certification Authorities, or the like, to enable key flashing in remote locations with only minor technical infrastructure. Introducing trusted mediator devices, new tokens can be authorized and later their public key can be flashed into a mobile system on demand.